التسويق الإسلامي منهج أخلاق متكامل: Islamic Marketing: An Integrated and Ethical Approach - Alzalook, Moneer Hosen; Lubis, Asmuliadi; Mansor, Fadillah (Journal Al-Muqaddimah, 2023)
The research deals with marketing from an integrated Islamic perspective, aiming to clarify the foundations, limitations and principles of marketing in Islam. Specifically, it focuses on consumer protection in the light of the unethical marketing practices prevalent in today’s market. The problem of the research addresses the unethical activities that are commonplace in the field of business and marketing. A qualitative research methodology was employed using descriptive narrative. The results show how the principles and ethics of an integrated Islamic approach to marketing help to mold human beings on sound foundations, guiding them to be upright and ethical in their dealings and their marketing. Consequently, sellers and consumers experience fairness and honesty, thereby creating a society based on brotherhood, faith and trust.